Household income and maternal education in early childhood and activity-limiting chronic health conditions in late childhood: findings from birth cohort studies from six countries. Issue 11 (21st July 2022) - Spencer, Nicholas James; Ludvigsson, Johnny; You, Yueyue; Francis, Kate; Abu Awad, Yara; Markham, Wolfgang; Faresjö, Tomas; Goldhaber-Fiebert, Jeremy; Andersson White, Pär; Raat, Hein; Mensah, Fiona; Gauvin, Lise; et al.
Abstract : Background: We examined absolute and relative relationships between household income and maternal education during early childhood (<5 years) with activity-limiting chronic health conditions (ALCHC) during later childhood in six longitudinal, prospective cohorts from high-income countries (UK, Australia, Canada, Sweden, Netherlands, USA). Methods: Relative inequality (risk ratios, RR) and absolute inequality (Slope Index of Inequality) were estimated for ALCHC during later childhood by maternal education categories and household income quintiles in early childhood. Estimates were adjusted for mother ethnicity, maternal age at birth, child sex and multiple births, and were pooled using meta-regression. Results: Pooled estimates, with over 42 000 children, demonstrated social gradients in ALCHC for high maternal education versus low (RR 1.54, 95% CI 1.28 to 1.85) and middle education (RR 1.24, 95% CI 1.11 to 1.38); as well as for high household income versus lowest (RR 1.90, 95% CI 1.66 to 2.18) and middle quintiles (RR 1.34, 95% CI 1.17 to 1.54). Absolute inequality showed decreasing ALCHC in all cohorts from low to high education (range: −2.85% Sweden, −13.36% Canada) and income (range: −1.8% Sweden, −19.35% Netherlands). Conclusion: We found graded relative risk of ALCHC during later childhood by maternal education and household income during early childhood in all cohorts. Absolute differences in ALCHC were consistently observed between the highest and lowest maternal education and household income levels across cohort populations. Our results support a potential role for generous, universal financial and childcare policies for families during early childhood in reducing the prevalence of activity limiting chronic conditions in later childhood.